Ejecución Presupuestaria del Gobierno Autónomo Descentralizado Parroquial de Balsapamba - Salazar Salazar, Anibal Javier (2018)
The present case study of a financial nature and social commitment to obtain the Degree in Accounting and Audit Engineering, deals with Budget Execution in the Parish Autonomous Decentralized Government of Balsapamba. The budgetary execution in the Parochial Decentralized Autonomous Governments is the implementation of the institutional plans to achieve optimal use of resources financial resources allocated in the budget for carrying out works, obtaining goods and services in quantity, quality and established time. The Autonomous Decentralized Parish Governments each year are assigned a certain budget for the realization of projects in favor of the community, due to the different problems that our country is going through, such as the low fall in the price of crude oil, This budget has decreased in a considerable way since 2016, which has Significantly affected in the execution of social projects and other competences institutional